Pengembangan Media Camat Pintar Melalui Video Animasi Bahasa Indonesia Kelas I MI Sidosari 2 Magelang - Muchamad Latif Mashud; Mulyani Rahayu; Setiarini Setiarini (STKIP Andi Matappa Pangkep, 2023)
The need for developing Camat pintar media through animated videos for students and teachers includes the need for videos that can be seen and heard well; can be used repeatedly according to time and place; can understand the presentation of information clearly, can contain the content of the material systematically and comprehensively; can improve student learning outcomes; Testing the effectiveness of the Indonesian language subject as sentence reading material for Class I students at MI Sidosari 2 Salaman, Magelang Regency. This research is R&D development research using ADDIE steps. The research results show that teachers and students need innovative, creative, interesting and easy to understand learning media that can improve student learning outcomes. The form of development is in the form of camat pintar media with animated videos through the steps of analysis, design, development, implementation and evaluation. Camat Pintar media with animated videos in Indonesian language subjects, material reading sentences, was proven to be effective in improving learning outcomes in Indonesian language subjects, material reading sentences (paired sample t test, p = 0.00 < 0.05).